Answer:
(x+3)^2=3
Step-by-step explanation:
First, you'll need to set this up.
(x^2+6x )+6 =0
We are going to solve the blank spaces now. The number next to the x is a 6. We need to find half of that which is 3. Next we need to square it which is 9. Here is how it looks like now.
(x^2+6x+9 )+6 =0
Next we need to find the next blank space, that will just be the same number of the first blank, just negative which would be -9.
(x^2+6x+9 )+6-9=0
Now we need to simplify! First we need to find the square of (x^2+6x+9). If you don't know how to do this, just say so in the comments! Anyways the square of this is (x+3)(x+3) or (x+3)^2.
So the equation now is (x+3)^2+6-9=0
Now, you need to do +6-9 which is -3.
The equation now is (x+3)^2-3=0
Now we need to put the -3 to the other side so (x+3)^2 can be isolated. So...
(x+3)^2-3=0
+3 +3
----------------------
(x+3)^2=3
THAT IS THE FINAL ANSWER! :) Hopefully this helped and making this answer "The Brainliest" would really help! Thank you and have a great day!